Follow-Up of Extended Shells around B[e] Stars - Liimets, Tiina (2022)
B[e] stars are massive B type emission line stars in different evolutionary stages ranging from pre-main sequence to post-main sequence. Due to their mass loss and ejection events these objects deposit huge amounts of mass and energy into their environment and enrich it with chemically processed material, contributing significantly to the chemical and dynamical evolution of their host galaxies. However, the large-scale environments of these enigmatic objects have not attracted much attention. The first and so far only catalog reporting the detection of extended shells around a sample of B[e] stars was an Hα imaging survey carried out in the year 2001, and was limited to bright targets in the northern hemisphere. We have recently started a follow-up of those targets to detect possible evolution of their nebulae in the plane of the sky over a baseline of two decades. Furthermore, we extend our survey to southern targets and fainter northern ones to complement and complete our knowledge on large-scale ejecta surrounding B[e] stars. Besides imaging in Hα and selected nebular lines, we utilize long-slit and 3D spectral observations across the nebulae to derive their physical properties. We discovered pronounced nebula structures around 15 more objects, resulting in a total of 27 B[e] stars with a large-scale nebula. Here we present our (preliminary) results for three selected objects: the two massive supergiants MWC137 and MWC 314, and the unclassified B[e] star MWC 819.